Effects of Lifestyle and Financial Literacy on the Financial Management Skill of Teenage Scouts - Dewi Agustin; Maretha Ika Prajawati (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2024)
This study investigates the impact of lifestyle and financial literacy on the financial management practices of teenage scouts in Malang City. Using a quantitative approach with a descriptive-correlational design, data were gathered from 135 teenage scout respondents through questionnaires and analyzed using multiple linear regression. The findings reveal that both lifestyle and financial literacy significantly influence financial management behavior. An excessive lifestyle negatively affects financial management outcomes, whereas strong financial literacy greatly enhances financial management practices. These results highlight the critical role of early financial education, particularly within scouting, in promoting responsible financial behavior among teenagers.